Project Feasibility Studies and Sustainability of Government Supported Projects in Uganda - Turyasingura John Bosco; Moses Agaba (International Journal of Business and social science ADPEBI, 2023)
The study investigated the impact of project feasibility studies on the sustainability of government-supported projects in Uganda using a case study of Parish Development Model in Kabale District. Project feasibility studies were an independent variable, while sustainability of government-supported projects was a dependent variable. Before the study started, a cross-sectional survey was done. 120 people participated in our survey, and we blended quantitative and qualitative analyses. The analysis was conducted on three separate levels and included descriptive, bivariate, and multivariate approaches. Because the descriptive analysis required the presentation of just one variable and its properties, frequency tables were used to illustrate the data. A Pearson correlation matrix was used to analyze the bivariate correlations between the dependent variable and the predictor components. Regression analysis results show that parish development models in Kabale District are more effective when participatory projects are implemented (coef = -0.715, p-value = 0.000). The main finding of this study is that project feasibility studies have a substantial impact on a parish development model project's sustainability. Parish Development Model initiators should focus more on including project beneficiaries in feasibility studies through project applicability, relevance, reliability, and acceptance to ensure the sustainability of all government-funded projects.